ChemInform Abstract: Organocatalytic One‐Pot Synthesis of Highly Substituted Pyridazines from Morita—Baylis—Hillman Carbonates and Diazo Compounds. Issue 35 (2nd September 2014) - Mao, Haibin; Lin, Aijun; Tang, Zhongkai; Hu, Hongwen; Zhu, Chengjian; Cheng, Yixiang
Abstract The title reaction proceeds via allylic alkylation and intramolecular diaza‐Wittig processes.